Socioecological determinants of dog ownership in Mara region, Tanzania - Danni Anderson; Maganga Sambo; Ahmed Lugelo; Anna Czupryna; Joel Changalucha; Jonathan M. Read; Felix Lankester; Katie Hampson (Preventive Veterinary Medicine, 2026)

The Impact of Disturbance on Tree Size Distributions in the United States - Adam J. Eichenwald; John M. Grady; Jonathan A. Knott; Quentin D. Read; J. Marcos Rodriguez; Sydne Record (Global Ecology and Biogeography, 2025)
Aim Tree size distributions are an emergent feature of forest dynamics across space and time. Theory suggests that undisturbed forests exhibit a size‐abundance distribution captured by a power‐law relationship with a near‐2 slope. We aimed to quantify how disturbances systematically and predictably cause deviations from this expected pattern. Location Contiguous United States. Time Period 2001–2023. Major Taxa Studied Diverse tree communities. Methods We analysed size‐abundance distributions in over 160,000 FIA plots for both disturbed and undisturbed forests, examining changes in slope associated with disturbances, stand age, and maximum tree height. We used a Structural Equation Model (SEM) to evaluate whether disturbance effects on size‐abundance slopes were indirectly mediated by changes in stand age or maximum height. Results We found that the predominant disturbances across the dataset (e.g., ground fires, animal damage) result in predictable flattening of size‐abundance slopes, reflecting the selective removal of smaller trees. In contrast, many disturbances (e.g., wind, disease) did not shift the slopes predictably, indicating that they did not selectively impact any specific size class. Maximum tree height and stand age were also reliable predictors of size‐abundance distributions, but a structural equation model demonstrated that the impact of disturbance on size‐abundance slopes was not mediated through its indirect effects on stand age or maximum tree height, suggesting a direct pathway of influence. Main Conclusions Disturbances result in predictable changes to forest size‐abundance slopes. As climate change and increased disturbance frequencies produce younger and shorter forests, future size‐abundance slopes are expected to be steeper than those in undisturbed forests. Our findings suggest a temporary flattening in the size‐abundance relationship immediately after the predominant disturbances across the dataset (ground fires, animal damage). These findings underscore the importance of understanding disturbance impacts on forest size structure to improve predictions of forests across broad spatial and temporal scales.

A horizon scan of biological conservation issues for 2025 - William J. Sutherland; Peter N.M. Brotherton; Holly M. Butterworth; Stewart J. Clarke; Tammy E. Davies; Nigel Doar; Nafeesa Esmail; Erica Fleishman; Kevin J. Gaston; James E. Herbert-Read; Alice C. Hughes; Jonathan Hughes; et al. (Trends in Ecology & Evolution, 2025)

The foraging ecology of green turtles (Chelonia mydas) in New Caledonia - Tyffen C. Read; Laurent Wantiez; Florent Keller; Jonathan M. Werry; Jason P. van de Merwe; Justin J. Meager; Olivier Chateau; Richard Farman; Colin J. Limpus (Marine Biology, 2024)
Green sea turtles ( Chelonia mydas ) face many threats from anthropogenic activity and are listed as Endangered on the International Union for the Conservation of Nature (IUCN) Red List of Threatened Species. They spend the majority of their lives in coastal foraging areas, and show strong fidelity to narrow foraging ranges. Understanding the foraging ecology of green turtles is therefore important for their management and conservation. Using stable isotopes analysis ( n = 200) and identification of stomach contents ( n = 21), this study investigated the foraging ecology of four distinct green turtle foraging aggregations (Goro, Isle of Pines, Ouen Island and Uo/Mato Islands) within the Grand Lagon Sud. This World Heritage Area located in New Caledonia supports regionally important nesting and foraging green turtle populations. The δ 13 C and δ 15 N values of skin samples ranged from − 19.3 to − 7.3‰ and 2.8–15.9‰, respectively. Metrics of isotopic niche and regression analyses were used to assess the degree of omnivory, trophic diversity and potential ontogenetic diet shifts in the different aggregations of foraging green turtles in this location. Each of the four sites and four age-classes had distinct isotopic niches, with evidence of omnivory and ontogenetic shifts, particular in new recruits and juveniles, and at Goro and Uo/Mato Islands. This was generally supported by the stomach contents analyses of a small number of green turtles opportunistically sampled from traditional ceremonies. This study provides important information on the foraging ecology of green turtles in New Caledonia, supporting management outcomes in this region. This collaboration with the tribes of the Grand Lagon Sud is also the first step towards the integrated management of the resource.

A horizon scan of global biological conservation issues for 2024 - William J. Sutherland; Craig Bennett; Peter N.M. Brotherton; Stuart H.M. Butchart; Holly M. Butterworth; Stewart J. Clarke; Nafeesa Esmail; Erica Fleishman; Kevin J. Gaston; James E. Herbert-Read; Alice C. Hughes; Jennifer James; et al. (Trends in Ecology & Evolution, 2024)

A global biological conservation horizon scan of issues for 2023 - William J. Sutherland; Craig Bennett; Peter N.M. Brotherton; Holly M. Butterworth; Mick N. Clout; Isabelle M. Côté; Jason Dinsdale; Nafeesa Esmail; Erica Fleishman; Kevin J. Gaston; James E. Herbert-Read; Alice Hughes; et al. (Trends in Ecology & Evolution, 2023)

Stochasticity generates an evolutionary instability for infectious disease - Jonathan M. Read; Matt J. Keeling (Ecology Letters, 2007)
Traditional models of disease evolution are based upon the deterministic competition between strains that confer complete cross‐immunity, and predict the selection of strains with higher basic reproductive ratios ( R 0 ). In contrast, evolution in a stochastic setting is determined by a complex mixture of influences. Here, to isolate the impact of stochasticity, we constrain all competing strains to have an equal basic reproductive ratio – thereby eliminating deterministic selection. The resulting stochastic models predict an evolutionary unstable strategy, which separates a region favouring the evolution of rapid‐transmission (acute) strains from one favouring persistent (chronic) strains. We find this to be a generic phenomenon with strain evolution consistently driven towards extremes of epidemiological behaviour. Even in the absence of an equal R 0 constraint, such stochastic selective pressures operate in addition to standard deterministic selection and will therefore influence the evolutionary behaviour of disease in all scenarios.